Netralitas Lembaga Kepresidenan : Membatasi Rangkap Jabatan Presiden, Gagasan Menuju Undang-Undang Lembaga Kepresidenan - Muhammad Sigit Ismail (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
The presidential institution is a crucial body within Indonesia’s constitutional system. Given its full and comprehensive authority, neutrality in the exercise of its power is essential. To safeguard this neutrality, it is necessary to limit the president from holding any other position outside the presidency. If the president concurrently holds another office, there is a concern that they may lose neutrality and act in favor of their own group, which could lead to public distrust toward the presidential institution and negatively impact the democratization process in Indonesia. Based on this condition, the formulated research problems are: what are the impacts and risks of the president holding multiple positions in government, and how should such dual roles ideally be restricted? The method used in this research is normative juridical, focusing on the study of secondary data. Based on the analysis conducted, it can be concluded that holding multiple positions can lead to unfavorable conditions in the performance of duties. Specifically, if the president concurrently holds another position that influences the government, it may damage the reputation of the presidential institution, as it creates the potential for unfairness and favoritism toward a particular group or interest. Therefore, limitations are necessary to prevent the president from holding other positions, which can be done by establishing legal norms to be included in legislation, such as constitutional amendments or the creation of a specific law regarding the presidential institution and related matters. This will help the presidential institution maintain its neutrality and independence.